Special Issue: Tissue Engineered Biomaterials and Drug Delivery Systems - Viviana P. Ribeiro; Joaquim M. Oliveira; Rui L. Reis (MDPI AG, 2022)
Current advances in biomaterials processing and engineering for drug delivery have allowed interesting progressed in biomedical field [...]